Improvement of Camel Milk Coagulation: Usefulness of an Enzymatic Extract from the Kaolin Layer of Chicken Gizzard - Sboui, Amel; Fguiri, Imen; Dbara, Mohamed; Hammadi, Mohamed; Khorchani, Touhami (Research Aspects in Agriculture and Veterinary Science Vol. 1, 2021)
This research was conducted aiming to improve the coagulation abilities of camel milk using an enzymatic extract from the Kaolin Layer (EKL) of chicken gizzards as a substitute to commercial rennet. The crude extract was prepared by dissolving dry Kaolin layer powder on a mixture of Nacl/CaCO3. The milk clotting activity (MCA) of the crude extract was determined basing to Berridge method. The EKL optimum coagulation conditions were as follows: pH=5, temperature=45°C; and a concentration of CaCl2: 0.09M. In addition, the enzymatic extract showed an important coagulant power mainly for camel milk: UP = 0.630 ± 0.04 against a coagulation frequency of 0.672 ± 0.05 for bovine milk. EKL can be used as a coagulant agent in cheese production for both camel and cow milk.